2007
DOI: 10.1097/01.hjh.0000254378.26607.1f
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of new-onset atrial fibrillation and its predictors with angiotensin II-receptor blockers in the treatment of hypertension and heart failure

Abstract: Atrial fibrillation is the most frequent occurring sustained cardiac arrhythmia and it is related to common cardiac disease conditions. Hypertension increases the risk of atrial fibrillation by approximately two-fold and, because of the high prevalence of hypertension, it accounts for more cases of atrial fibrillation than any other risk factor. In recent years, there are two large hypertension trials (LIFE and VALUE) and two large heart failure trials (CHARM and Val-HeFT) reporting the beneficial effect of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 67 publications
2
22
0
2
Order By: Relevance
“…34,35 The benefit of renin-angiotensin inhibition in heart failure has been demonstrated in several randomized clinical trials. We have previously shown that the hypertrophy in the TG mice can be reversed by pharmacological suppression of the RAS, and future studies are required to determine whether reversal of ECC remodeling can be achieved by these means.…”
Section: Significance and Limitations Of The Modelmentioning
confidence: 99%
“…34,35 The benefit of renin-angiotensin inhibition in heart failure has been demonstrated in several randomized clinical trials. We have previously shown that the hypertrophy in the TG mice can be reversed by pharmacological suppression of the RAS, and future studies are required to determine whether reversal of ECC remodeling can be achieved by these means.…”
Section: Significance and Limitations Of The Modelmentioning
confidence: 99%
“…Recientemente se ha centrado la atención en la medición ecocardiográfica del tamaño auricular izquierdo como frecuente indicio de hipertrofia ventricular izquierda 374 y como predictor de los episodios cardiovasculares 375 , en paralelo con la evidencia creciente de que los fármacos antihipertensivos pueden tener efectos diferentes en el desarrollo de la fibrilación auricular 376 . Dos ensayos amplios en la hipertensión 377,378 han indicado que los antagonistas de los receptores de la angiotensina losartán y valsartán se asocian a una menor incidencia de fibrilación auricular de nueva aparición, en comparación con el bloqueador beta atenolol y el antagonista del calcio amlodipino, respectivamente.…”
Section: Corazónunclassified
“…Parece que es necesario un estricto control de la presión arterial cuando se administra un tratamiento anticoagulante, debido a que los ictus y los episodios hemorrágicos son más frecuentes cuando la presión arterial sistólica es ≥ 140 mmHg 629 . A la vista de los resultados obtenidos en análisis post-hoc de 2 ensayos recientes [376][377][378] , que indican menos incidencia de fibrilación auricular de nueva aparición con los antagonistas de los receptores de la angiotensina (véase el apartado 4.5.1), estos fármacos pueden ser preferibles, aunque es deseable obtener una confirmación en los ensayos clínicos en curso.…”
Section: Fibrilación Auricularunclassified
“…4,10,11 Increased pulse pressure (PP), defined as the difference between systolic blood pressure (SBP) and diastolic blood pressure (DBP), is a marker of arterial stiffness.…”
mentioning
confidence: 99%
“…9 Prevention of AF is thus of great importance, and hypertension is currently the most prevalent, potentially modifiable risk factor, accounting for Ϸ14% to 22% of AF cases. 4,10,11 Increased pulse pressure (PP), defined as the difference between systolic blood pressure (SBP) and diastolic blood pressure (DBP), is a marker of arterial stiffness. 12 Studies have found PP to be an independent predictor of new-onset AF in both general 13 and hypertensive 14 populations.…”
mentioning
confidence: 99%